Ecology of Absence - Larson, Brooke (2016)
The article discusses the Anasazi Foundation, a wilderness therapy program and philosophical group founded by Ezekiel Sanchez and Larry Olson. Topics include Navajo traditions, wilderness of deserts, and philosophy behind absence. Also discussed is the lack of consciousness and positive aspects of blandness
Keywords: ANASAZI Historical Site (Utah); Deserts -- Religious aspects -- Christianity; NAVAJO (North American people); OLSON, Larry; Presence (Philosophy); SANCHEZ, Ezekiel; SOCIAL life & customs; Wilderness (Theology)